Pemanfaatan Lahan Pekarangan untuk Memenuhi Kebutuhan Keluarga di Desa Cintalaksana, Kecamatan Tegalwaru, Kabupaten Karawang - Ananda Diah Oktaviani; Novita Niken Putri Ulayyah; Titiek S. Yuliani; Megayani Sri Rahayu; Iskandar Lubis; Fitriyah Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Cintalaksana Village is a village located in Tegalwaru District, Karawang Regency, West Java Province. This village has a land condition that fluctuates (terraces) and the average high rainfall is 2,600 mm-4,500 mm per year. This makes it possible to develop the agriculture, livestock and tourism sectors. The Sustainable Family Yard Program (PKL) aims at the residents of Cintalaksana Village to be able to utilize their home yards by planting TOGA, ornamental plants, fruit plants, and vegetable crops as well as the residents' houses which are used as a pilot to provide benefits to surrounding residents. The Sustainable Family Home Program (PKL) begins with licensing for village officials to carry out activities that involve residents and use vacant land owned by the head of RT 01, the village head, and the Lotus Posyandu 1. After the permit is completed, continue to clean up the empty land that has been overgrown with weeds using weeds using hoe. After that the making of beds in the land to sow kale and spinach seeds. For seedbed chillies use a polybag filled with a mixture of soil planting media and manure. After all the seeds are sown, watering is done until the soil becomes moist. Making verticulture using old bottles which are then planted with Alternanthera brasiliana and Portulaca ornamental plants. The implementation of the Sustainable Family Home Program (PKL) program in Cintalaksana Village went well. Residents began to realize the importance of utilizing vacant land around the house to become a sustainable yard. The yard can be planted with various types of plants so that it can meet food needs as well as the family economy. Keywords: Cintalaksana Village, family medicinal plants, yards